Flouting and Violation Grice’s Theory of Cooperative Principle Maxim in Podcast Dedy Corbuzier Scene Widi Viera-Cinta Laura - Nadya Insani Sidabutar; Lastri Wahuni Manurung; Rina Octavia Simarmata (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
In communication, people should be cooperative to avoid misunderstanding. Meanwhile, from the non-cooperation of Grice's theory of cooperative principle. Violating maxim means the speaker does not observe the maxim not in purpose. The flouting maxim implies that the speaker does not observe the maxim purposefully. This research analyzes the non-cooperative principle used by Podcast Dedy Corbuzier Scene Widi Viera-Cinta Laura. The researcher chooses this podcast because it can involves a conversation between a host and a guest star that discuss about a certain topic, the speaker might break the maxim of cooperative principle in delivering the message and providing information to the listener. This research was conducted by using descriptive qualitative. The present study aims 1) To find out flouting and violation maxim are used in Dedy Corbuzier’s YouTube Channel, and 2) To describe the reason why flouted and violation maxims occur in Podcast Dedy Corbuzier scene Widi Viera – Cinta Laura. The results that the researcher found are that out of 36 data, 14 were flouting a maxims, 22 were violation a maxims. From the result above, violation maxim was the most similar. Violating maxim means the speaker does not observe the maxim not in purpose , maxim quantity that cause speakers not to give enough information to a listener. Whereas in Flouting maxim happened because the speakers failed to obey maxim on purpose. Based on the data of flouting maxim of realtion most dominantly used that causes speakers want to change the topic and reveal the hidden meaning behind the utterances.